Emotional intelligence of university men and women in Juliaca city - Gutiérrez Echegaray, Carliño Engut (2022)
Objective: To determine the difference in the levels of Emotional Intelligence between universitywomen and men in the city of Juliaca, 2021. Methodology: Quantitative approach of comparativedescriptive type, non-experimental design, cross-sectional. On the other hand, the study populationwas comprised of 208 people; 113 women and 95 men; that they are studying university education withages between 16 and 18 years of age, for data collection the instrument called “BarON-ICE EmotionalIntelligence Inventory, NA” was used in its entirety; adapted and standardized by Nelly Ugarriza inPeru. This instrument has 5 dimensions which are: Intrapersonal, Interpersonal, Adaptability, StressManagement, General Mood. Results: At the conclusion of this investigation, an Emotional Intelligencevalue of (p=0.00) was found in the results, thus demonstrating that if there is a difference in the levelof emotional intelligence of university women and men from Juliaca, it should also be noted that theresult is more favorable to the female gender, in parallel in the different dimensions that are evaluatedtogether; Results were obtained that tell us that in dimensions such as: Intrapersonal, Interpersonaland Stress Management, if there is a difference between women and men, in turn in dimensions suchas: Adaptability and Mood in General, there are no significant differences between women and men.university students from the city of Juliaca.